One‐minute heart rate variability – an adjunct for airway obstruction identification. Issue 1 (10th January 2019) - Lehavi, Amit; Golomb, Neta; Leiba, Ronit; Katz, Yeshayahu (Shai); Raz, Aeyal
Abstract: Heart rate variability (HRV) reflects cardiac and autonomic nervous system activity. It is usually measured over a relatively prolonged period and presented using multiple parameters. Here, we studied rapid HRV changes during airway obstruction using a short (1 min) sampling window. Forty healthy volunteers underwent a trial of obstructed breathing. Heart rate was recorded during three consecutive sets comprised of 1‐min control followed by 1 min of obstructed breathing, with 1 min of rest between sets. Time and frequency domain analysis were used to compare HRV during control versus obstructed breathing.C ompared with control, HRV intensely increased during obstructed breathing: R‐R intervals (time between consecutive R waves) standard deviation increased from 65 to 108 msec ( P < 0.0001), root mean square of successive R‐R interval from 61 to 82 msec ( P = 0.001), number of pairs of successive R‐R intervals that differ by more than 50 msec (NN50) from 16.5 to 25.3 events ( P < 0.0001), and proportion of NN50 divided by total number of R‐R intervals from 26.6 to 35.1% ( P = 0.001). Low frequency power increased by more than fourfold ( P < 0.0001), allowing 90% sensitivity and 75% specificity for identifying airway obstruction (ROC area 0.88, P < 0.0001). We observed a rapid intense increase in HRV during obstructed breathing, significant enough to detect during a short 1‐min sampling window. These findings suggest that HRV may be useful for rapid detection of airway obstruction, especially in situations where end‐tidal CO2 monitoring is not optimal, such as during partial airway obstruction. Abstract : We measured heart rate variability (HRV) changes during a trial of airway obstruction using a short (1 min) sampling window in 40 healthy volunteers. Using multiple HRV measures we observed a rapid intense increase in HRV during obstructed breathing, significant enough to detect during a short 1‐min sampling window.